A method of making a uco fuel core
Patent Information
- Application Number
- CN202511773688.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明的目的是提供一种UCO燃料核芯的制备方法,从而解决现有技术中无机碳源分散不均易导致凝胶球破裂或堵塞针头、有机碳源易与胶体反应且水洗时易流失,均难以制备元素分布均匀的 UCO 燃料核芯的问题
[0038]水解缩聚反应的反应速率主要通过反应温度和搅拌速度来进行控制,通过pH值评判水解缩聚反应是否充分,待溶胶溶液降温至室温后,均匀分散有机碳源到溶胶中,有机碳源的高溶解度有效提高了含碳源溶胶的均匀性和稳定性,降低的pH通过滴加氨水来调节,最后通过增稠剂聚乙烯醇来调节粘度,有效改善了溶胶胶粒的稳定性和凝胶机械强度。
Smart Images

Figure CN122991701A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nuclear energy technology, and more specifically to a method for preparing a UCO fuel core. Background Technology
[0002] UCO (UCx-UO2) is internationally recognized as a new type of nuclear fuel that provides superior performance for Generation IV high-temperature gas-cooled reactors at higher operating temperatures. UCO fuel is an advanced fuel design that "maximizes strengths and minimizes weaknesses." It sacrifices some of the performance advantages of UC... x The extreme thermal conductivity and uranium density resulted in far superior performance compared to UC. x It exhibits superior radiation stability and chemical compatibility. Furthermore, it significantly outperforms traditional UO2 fuel in terms of thermal performance and uranium density. Therefore, in next-generation nuclear energy systems seeking higher efficiency, greater safety, and longer lifespan, UCO fuel demonstrates superior performance compared to single UO2 or UC fuels. x The fuel boasts superior overall performance and enormous application potential.
[0003] Typically, UCO is prepared from carbon-containing UO2 via a carbothermal reduction reaction, while carbon-containing UO2 microspheres are formed through a wet chemical gelation process. Currently, methods for preparing uranium carbon oxide cores usually employ inorganic or organic carbon sources as the basis for the carbothermal reaction to generate UC. x The raw materials are as follows: Inorganic carbon sources include carbon black and nano-graphite powder; organic carbon sources include fructose, sucrose, and citric acid. Because inorganic carbon sources have large particle sizes, they are difficult to disperse evenly in sols, leading to problems such as gel sphere breakage or clogging of the dispersion head during colloid formation. Even if formation is successful, excessive internal pores in the microspheres may affect the core's microstructure and performance. Compared to inorganic carbon sources, organic carbon sources have good water solubility, making them easier to disperse evenly in colloids and obtain complete gel spheres. However, organic carbon sources may react chemically with the colloid, altering the colloid's chemical properties and affecting gel sphere formation. Furthermore, the resulting gel spheres may experience carbon source dissolution and loss in aged ammonia solutions.
[0004] Gao Yong et al. used sucrose as an organic carbon source to prepare ZrO2-ZrC ceramic microspheres using internal gelation technology. The study found that compared with inorganic carbon source TS-10 carbon, the preparation of core microspheres with sucrose as an organic carbon source does not produce large carbon particles or cause carbon particle aggregation. However, the carbon loss during the water washing process cannot be ignored. When sintered microspheres were prepared with low concentration of added sucrose, they showed a core-shell structure with ZrC as the inner layer and ZrO2 as the outer layer, which also confirmed that sucrose was lost during the washing process. The proportion of ZrC in the final sintered microspheres was also lower than the theoretical value, which led to the uncontrollable microstructure uniformity and final oxide carbide composition ratio of the microspheres under the process conditions (Ceramics International 42 (2016) 4715–4722).
[0005] In summary, current carbon source dispersion and carbothermic reduction processes cannot prepare uniformly elementally distributed UO2-UC through simple process flows. x Fuel core.
[0006] Therefore, it is necessary to develop an improved organic carbon source that can maintain the spheroidizing properties of the colloid, have a sufficiently strong chemical interaction with the heavy metal matrix to prevent carbon source loss, and effectively improve the performance of UCO fuel cores. Summary of the Invention
[0007] The purpose of this invention is to provide a method for preparing UCO fuel cores, thereby solving the problems in the prior art where uneven dispersion of inorganic carbon sources easily leads to gel sphere rupture or needle blockage, and organic carbon sources are prone to reaction with colloids and easy to be lost during water washing, both of which make it difficult to prepare UCO fuel cores with uniform elemental distribution.
[0008] To solve the above problems, the present invention adopts the following technical solution:
[0009] A method for preparing a UCO fuel core is provided, comprising the following steps: S1, under heating conditions, nitric acid is added to UO2 or U3O8 powder to dissolve and form a uranyl nitrate solution; urea is added and heated to react and form a hydrolysis solution; an organic acid-based organic carbon source capable of chelating with uranium ions is added to the hydrolysis solution and stirred thoroughly to disperse it evenly; ammonia is added dropwise to adjust the pH of the solution to 2.1-2.5; then tetrahydrofurfuryl alcohol and a thickener polyvinyl alcohol solution are added and stirred to form a uranium-based precursor solution containing an organic carbon source; S2, the uranium-based precursor solution containing an organic carbon source is further processed. The uranium-based precursor solution of organic carbon source is dispersed into droplets by a vibrator. The droplets pass through an air section and an ammonia section in sequence and then fall into ammonia water to form gel microspheres. S3, the gel microspheres are placed in concentrated ammonia water for static aging. They are first washed with dilute ammonia water until the conductivity remains unchanged, and then washed with deionized water. The washed gel microspheres are spread in a single layer in a drying furnace and dried by step-by-step temperature increase to obtain dried gel microspheres. S4, the dried gel microspheres are placed in a sintering furnace and sintered under an inert gas atmosphere to obtain UCO ceramic core containing UO2 and UC components.
[0010] Preferably, in step S1, the uranyl nitrate solution is an acid-deficient uranyl nitrate solution, and the preparation process includes: dissolving UO2 or U3O8 powder with nitric acid, stirring and heating to 75~90°C, slowly adding solid urea in batches to the uranyl nitrate solution for hydrolysis reaction for 36~50h, cooling to room temperature after the reaction is completed, and then adding the organic acid-based organic carbon source; the uranium-based precursor solution containing the organic carbon source needs to be ultrasonically degassed before dispersion to eliminate bubbles.
[0011] Preferably, in step S1, the concentration of the uranyl nitrate solution is 1.4~2.2 mol / L; the molar ratio of urea / U(VI) is (2~3.4):1; and the molar ratio of nitric acid to UO2 powder is (1.7~1.9):1.
[0012] Preferably, the molar ratio of carbon content to uranium metal ions in the organic carbon source [C] / [U] is (0.5~3.5):1; the organic carbon source is added to the hydrolysis solution at room temperature (15~25℃) and dispersed evenly.
[0013] It should be understood that the molar ratio of carbon to uranium [C] / [U] in organic carbon sources is a core process parameter: if this ratio is too low, the carbon supply in the carbothermic reaction is insufficient, and the final product contains only UO2 and no UC component; if the ratio is too high, the carbon content is excessive, which may result in the final product containing only UC and no UO2 component.
[0014] According to a preferred embodiment of the present invention, the organic acid-based organic carbon source is ascorbic acid. However, it should be understood that this is merely an example and not a limitation, and the organic carbon source applicable to the present invention is not limited to ascorbic acid. Any organic acid that can chelate with uranium ions can be used as the organic carbon source in the preparation method of the present invention, such as ascorbic acid, citric acid, malic acid, tartaric acid, etc.
[0015] According to a preferred embodiment of the present invention, step S1 specifically involves: dissolving UO2 or U3O8 powder by reacting it with concentrated nitric acid for about 1 hour to prepare a uranyl nitrate solution; adding urea in batches while heating and stirring at 75-90 °C; and reacting for 36-48 hours. The solution is then cooled for use.
[0016] The concentration of uranyl nitrate solution is 1.4~2.2 mol / L; the molar ratio of CO(NH2)2 / U(VI) is (2~3.4):1; the obtained precursor solution is adjusted to a uranium metal ion concentration of 1.0~1.4 mol / L by adding urea; the uranyl nitrate solution is hydrolyzed by adding urea at 70~90°C to form a hydrolyzed solution; the endpoint is reached when the pH of the obtained hydrolyzed solution is 2.75~3.2.
[0017] The hydrolysate was cooled to room temperature, and ascorbic acid with a C / U molar ratio of (0.5~3.5):1 was added. The mixture was stirred for 1.5 h until fully dissolved. Ammonia was then added to adjust the pH to 2.1~2.5, followed by the addition of tetrahydrofurfuryl alcohol, which reacts with [UO2] 2+ The dosage ratio is 0.2~0.5∶1.
[0018] Preferably, an 80-120 g / L polyvinyl alcohol solution after defoaming is added at 15-30°C to increase the viscosity of the sol. The viscosity of the sol is adjusted to 50-75 mPa·s at 25°C using a viscometer, wherein the concentration of polyvinyl alcohol in the sol is approximately 5 g / L-25 g / L.
[0019] According to a preferred embodiment of the present invention, step S2 specifically involves: delivering the sol to the pipeline via a pressure controller, and dispersing the continuous sol into droplets via a vibrator, with the droplets dripping from the needle tip and pre-curing at the ammonia gas distribution ring of the gelation column.
[0020] The flow rate of the gas-transported sol is 5~12 mL / min, the frequency of the exciter is 15~60 Hz, the inner diameter of the needle is 0.4~0.6 mm, and the ammonia flow rate is 5 L / h~30 L / h.
[0021] According to a preferred embodiment of the present invention, step S3 specifically comprises: aging the gel microspheres in concentrated ammonia water, washing them with 0.5M dilute ammonia water until the conductivity remains constant, then washing them five times with deionized water. The washed gel microspheres are then spread in a monolayer in a drying oven, and the heating rate is set to 0.5~1°C / min. The temperature is gradually increased to 80°C, 90°C, 100°C, and 200°C, and held at these temperatures to remove free and bound water from the gel microspheres, resulting in dry gel particles. It should be understood that if the heating rate is too fast, the gas inside the gel microspheres cannot be expelled in time, which can easily cause the microspheres to rupture, leading to a decrease in the yield of the finished product.
[0022] Preferably, the gel microspheres are placed in concentrated ammonia water at 5~27°C for 8~14h for aging, washed with 0.5mol / L dilute ammonia water until the conductivity remains unchanged, and then washed 5 times with deionized water.
[0023] Preferably, the washed gel microspheres are spread in a single layer in a drying oven, and the heating rate is 0.3~1°C / min. The heating program is as follows: keep at 80 °C and 90 °C for 0.5~1 h each, and keep at 100 °C and 200 °C for 2~3 h each.
[0024] Step S4 specifically involves: spreading the dried gel microspheres flat in a sintering furnace, heating to 1650~1950°C for calcination and sintering, and then cooling to obtain dense ceramic microspheres.
[0025] The furnace chamber is evacuated, and then a certain amount of argon gas is introduced to maintain a positive pressure. The air flow rate is 70-100 L / h. The heating program is as follows: room temperature to 1600°C, 3°C / min, holding at 400°C, 800°C, 1200°C, and 1600°C for 1 hour each; 1600-1650 / 1950°C, 5°C / min, holding for 3-6 hours. It should be understood that if air is mixed into the atmosphere, the carbon source in the microspheres will undergo oxidation, preventing the formation of UC. The sintering temperature and holding time directly affect the density of the final product. Too low a temperature makes it difficult to form a good ceramic phase, and the product density is low; too high a temperature leads to energy waste and poses safety hazards.
[0026] This invention employs a carbothermal reduction combined with external gelation technique using an organic carbon source. The apparatus is simple, the carbon source exhibits good uniformity of dispersion, and the sphere formation rate is high. The obtained UCO ceramic microspheres are a mixture of uranium dioxide and uranium carbide. The chemical formula of this mixture of uranium dioxide and uranium carbide is UO2-UC. x , where x is 1, 1.8, or 2. The diameter of the UCO ceramic microspheres ranges from 300 μm to 1.0 mm.
[0027] Combination Figure 1 As shown, the preparation process of UCO ceramic microspheres according to the present invention is described in detail below:
[0028] First, UO2 or U3O8 powder is reacted with nitric acid to dissolve it and form a uranyl nitrate solution with low acidity. The prepared uranyl nitrate solution is then reacted with urea to form uranium colloid.
[0029] Then, an organic carbon source that can chelate with uranium ions (such as ascorbic acid) is dispersed into the uranium colloidal solution and stirred thoroughly. The ascorbic acid reacts with UO2. 2+ The ions undergo chelation to form a stable metal complex in aqueous solution. A small amount of ammonia is added to adjust the pH.
[0030] Add an appropriate amount of tetrahydrofurfuryl alcohol and thickener PVA. Tetrahydrofurfuryl alcohol undergoes an esterification reaction with the complex to obtain a polymer resin, forming an acid-containing colloid.
[0031] Next, the acid-containing colloid is dispersed into droplets through a vibrator. The droplets solidify under the action of ammonia gas and fall into ammonia water to form gel microspheres.
[0032] Then, the gel microspheres were aged in concentrated ammonia water, washed with dilute ammonia water and deionized water, and the washed gel microspheres were spread in a single layer in a drying oven to obtain dried gel microspheres.
[0033] Finally, the dried gel microspheres were placed in a sintering furnace and calcined and baked in an inert atmosphere (such as argon or CO) to obtain UCO ceramic microspheres.
[0034] In summary, according to the preparation method provided by the present invention, uranyl nitrate solution is prepared by oxidizing and dissolving U3O8 or UO2 powder with nitric acid, and then uranium sol is prepared by hydrolysis and condensation reaction by adjusting the pH with urea. Organic acids such as ascorbic acid are used as organic carbon sources and dispersed into the sol solution. The pH of the colloid is adjusted with ammonia water, and the viscosity is adjusted with polyvinyl alcohol as a thickener. Then, UCO ceramic microspheres can be obtained through processes such as transportation and dispersion, aging and washing, drying and calcination.
[0035] It should be understood that in the preparation method of the UCO fuel core provided by this invention, the addition of an organic carbon source (such as ascorbic acid) capable of chelating with uranium ions and the thorough stirring steps are crucial. The purpose is to ensure that uranium ions and the organic carbon source undergo a sufficient chelation reaction, which is a core prerequisite for achieving molecular-level uniform mixing. Insufficient reaction will lead to insufficient stability of the carbon source during subsequent water washing. It should also be understood that the pH adjustment step of the ammonia water after the addition of the organic carbon source is equally critical, as the addition of the carbon source alters the pre-neutralization degree of the colloid. Without readjusting the pH value, it will be difficult to obtain high-performance gel spheres during subsequent dispersion.
[0036] The key inventive point of this invention lies in using organic acids that can chelate with uranium ions as organic carbon sources to prepare UCO cores. The good water solubility of organic acids and organic carbon sources improves the yield of core preparation, reduces the economic cost of producing UCO fuel cores, and at the same time ensures the quality and performance of the cores, making it suitable for the manufacture of high-temperature gas-cooled reactor fuels.
[0037] Compared with existing technologies, the method for preparing a UCO fuel core according to the present invention has the following advantages:
[0038] The reaction rate of the hydrolysis-condensation reaction is mainly controlled by the reaction temperature and stirring speed. The pH value is used to judge whether the hydrolysis-condensation reaction is sufficient. After the sol solution is cooled to room temperature, the organic carbon source is uniformly dispersed into the sol. The high solubility of the organic carbon source effectively improves the uniformity and stability of the carbon source-containing sol. The pH is adjusted by adding ammonia water. Finally, the viscosity is adjusted by the thickener polyvinyl alcohol, which effectively improves the stability of the sol particles and the mechanical strength of the gel.
[0039] Using ascorbic acid as an organic carbon source in the subsequent carbothermic reduction reaction of the gel spheres effectively prevents changes in the colloidal properties of metal ions caused by the low water solubility of inorganic carbon sources, ensuring good sphericity of the gel spheres, solving the problem of carbon source clogging pinholes during microsphere dispersion, and reducing the probability of deformed UCO ceramic microspheres. Based on the complexation effect between organic carbon sources such as ascorbic acid and uranyl ions, they can be chemically bonded and fixed in the UCO gel network framework. This chemical bonding can effectively reduce the loss of carbon source during washing, thereby preventing the inhomogeneity of the gel microsphere structure caused by washing and its fragmentation during subsequent heat treatment. It also helps to accurately control the [C] / [U] ratio of the final ceramic microsphere product.
[0040] This invention, through experimental characterization, discovered the complexation effect between ascorbic acid and uranyl ions. Compared with other organic carbon source systems such as glucose and sucrose, the stability of ascorbic acid was significantly improved during water washing, and the loss was greatly reduced. Common organic carbon sources typically use monosaccharides (such as fructose and glucose) or polysaccharides (such as sucrose). Ascorbic acid is often used as a dispersant, and its acidity may affect the properties of the colloid, so it is rarely considered as a carbon source. It is also only used in the preparation of powder or bulk fuels. The chelation structure in this invention achieves uniform and tight mixing of the carbon source and uranium source at the molecular scale. This solves the problem of easy loss of common carbon sources such as fructose, glucose, and sucrose during water washing. Furthermore, furfuryl alcohol is added to induce a polyesterification reaction with the complex, ensuring uniform dispersion of elements and avoiding the problem of unstable colloidal properties due to uneven mixing.
[0041] Ascorbic acid, citric acid, malic acid, and tartaric acid are a class of natural, non-toxic organic compounds that are environmentally friendly and inexpensive. Using them as carbon sources can prevent the introduction of harmful impurities at the source, significantly improve the environmental friendliness of the preparation process, highly align with the concept of green chemistry, and reduce the economic cost of production.
[0042] During the drying process, a stepped heating and holding process (e.g., holding at 80°C, 90°C, 100°C, and 200°C sequentially) effectively suppressed the internal stress caused by rapid evaporation of moisture inside the microspheres, thus preventing the microspheres from breaking. High-temperature calcination and sintering at 1200°C~1950°C allowed ascorbic acid to undergo a carbothermic reduction reaction with some UO2 after high-temperature carbonization, generating UC. x The final obtained UO2-UC xThe hybrid ceramic microspheres exhibit uniform particle size, smooth and intact surface, ceramic metallic luster, dense structure, and uniform elemental distribution, with a density exceeding 78%, reaching up to 97% TD. However, it should be understood that the density of spherical fuel particles must balance performance requirements; the optimal density is typically 95%–97% of the theoretical density. Excessive density or inadequacy will negatively impact performance. Excessive density leads to decreased mechanical properties, increased particle brittleness, and easy breakage, and the extremely low internal porosity prevents effective storage of fission gases generated during irradiation, easily causing particle swelling and rupture. Conversely, insufficient density results in lower uranium content per unit volume, inadequate fuel loading, and reduced reactor power output. Furthermore, excessive porosity leads to insufficient particle structural strength, making them susceptible to irradiation damage and high-temperature corrosion. The UCO ceramic microspheres prepared according to this invention achieve a balance between performance requirements.
[0043] Literature (Ceramics International 42 (2016) 4715–4722) shows that the SEM images of the cross-section of sintered microspheres prepared with inorganic carbon source TS-10 exhibit obvious porous structures. However, sintered microspheres prepared with sucrose as the carbon source suffer carbon source loss during the front-end water washing process, resulting in a core-shell structure with an outer oxide layer and an inner carbide layer, leading to uneven elemental distribution. This invention uses a particle size and shape analyzer to test the sphericity of 50 randomly sampled microspheres, obtaining a sphericity of 1.02 ± 0.2. Energy dispersive X-ray spectroscopy (EDS) was used to determine the micro-area elemental distribution of the cross-section of the sintered UCO microspheres, showing that the three UCO components are distributed very uniformly throughout the microsphere cross-section. Therefore, the UCO ceramic microsphere preparation method provided by this invention, which uses ascorbic acid and other organic carbon sources to prepare UCO mixed oxide fuel, has the advantages of good sphericity and uniform elemental content distribution.
[0044] In summary, this invention, by optimizing the organic carbon source addition process, not only achieves a high-density and uniform microstructure in the UCO fuel core, but also improves carbon source utilization and reduces economic costs. The UCO ceramic microspheres obtained using this method are characterized by uniform particle size, smooth and intact surface, excellent sphericity, uniform elemental distribution, and dense structure. Furthermore, the preparation method of this invention is low-cost, has a high sphericity rate, and allows for flexible control of the molar ratio of carbon to uranium [C] / [U], thereby preparing UCO fuels with different component ratios. It is suitable for the preparation of various micron-sized UCO ceramic microspheres. Attached Figure Description
[0045] Figure 1 This is a flowchart of a method for preparing UCO ceramic microspheres according to the present invention;
[0046] Figure 2 This is an optical micrograph of the UCO ceramic microspheres prepared in Example 1 of this invention;
[0047] Figure 3 This is an EDS elemental distribution diagram of the UCO ceramic microspheres prepared in Example 1 of this invention. Detailed Implementation
[0048] The present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, the techniques used in the embodiments are conventional practices in the art, or experimental methods recommended by instrument manufacturers. Unless otherwise specified, the reagents and materials used in the embodiments are commercially available.
[0049] Example 1:
[0050] According to this embodiment, a UCO ceramic microsphere is prepared by the following method:
[0051] 1. Preparation of uranium colloid: Weigh 48.60 g of UO2 powder and add it to 4 mol / L nitric acid. Heat at 85°C to dissolve and prepare 100 mL of 1.8 mol / L uranyl nitrate solution. Raise the temperature to 85°C and slowly add 32.4 g of urea in batches, stirring until completely dissolved to prepare a yellow transparent uranium sol solution. Cool to room temperature and disperse 15.84 g of ascorbic acid into the colloidal solution, stirring for about 1.5 h until fully dissolved. Then, add ammonia water dropwise to adjust the pH to 2.3. While stirring, add 10 mL of tetrahydrofurfuryl alcohol and 40 mL of 100 g / L polyvinyl alcohol. Stir until completely homogeneous, let stand, and sonicate to eliminate bubbles to obtain a uranium colloidal solution containing an organic carbon source.
[0052] 2. Vibration dispersion molding: The colloidal solution containing carbon source is transported to the pipeline by gas, then dispersed into droplets by the vibrator, and then passed through the air zone and the ammonia zone in sequence, and finally fell into the ammonia water to form gel microspheres.
[0053] 3. Aging, Washing, and Drying: The gel microspheres were soaked in concentrated ammonia water for 12 hours. They were then washed with dilute ammonia water at room temperature until the conductivity remained constant, followed by five washes with deionized water. After equilibration with deionized water for 3 hours, the conductivity of the washing solution was measured to be 7 μS / cm. The washed gel microspheres were then spread in a monolayer and transferred to a drying oven. The following stepped heating program was set: heating rate of 1°C / min, holding at 80°C for 1 hour, holding at 90°C for 1 hour, holding at 100°C for 2 hours, and holding at 200°C for 2 hours, with a cooling rate of 2°C / min, to obtain intact dried gel microspheres.
[0054] 4. Sintering: The dried gel microspheres were transferred to a high-temperature furnace. A vacuum was first created, followed by the introduction of a certain amount of argon gas to maintain a positive pressure within the furnace tubes. The argon gas flow rate was 70 L / h. The heating program was as follows: room temperature to 400°C, 3°C / min, hold for 1 hour; 450 to 800°C, 3°C / min, hold for 1 hour; 800°C to 1200°C, 3°C / min, hold for 1 hour; 1200°C to 1600°C, 3°C / min, hold for 1 hour; 1600°C to 1800°C, 5°C / min, hold for 3 hours; 1800°C to room temperature, allow to cool naturally. Black UCO ceramic microspheres with a iridescent ceramic luster were obtained, with a density of 69.9% TD. At this point, the UC content was 34.3%, and the UO2 content was 65.7%.
[0055] like Figure 2 As shown, the UCO ceramic microspheres prepared according to this embodiment have a smooth and flat surface, exhibit a ceramic metallic luster, uniform particle size, and good quality.
[0056] like Figure 3 As shown, EDS elemental analysis of the microsphere cross-section reveals a highly uniform distribution of U, C, and O elements within the ceramic microsphere. This is attributed to the excellent water solubility of ascorbic acid as an organic carbon source and the chelate structure between ascorbic acid, uranyl ions, and furfuryl alcohol, which enables a uniform and close mixing of the carbon and uranium sources at the molecular scale. This is also an advantage of using organic carbon sources to prepare UCO ceramic microspheres.
[0057] Example 2:
[0058] According to this embodiment, a UCO ceramic microsphere is prepared by the following method:
[0059] 1. Preparation of uranium colloid: Weigh 44.91 g of U3O8 powder and dissolve it in 5 mol / L nitric acid at 90°C to prepare 100 mL of a 1.6 mol / L uranyl nitrate solution. Heat the solution to 85°C and slowly add 30.72 g of urea in batches, stirring until completely dissolved to form a yellow, transparent uranium sol solution. Cool to room temperature and disperse 14.55 g of ascorbic acid into the colloidal solution, stirring for about 1.5 h until fully dissolved. Then, adjust the pH to 2.4 by adding ammonia dropwise. While stirring, add 10 mL of tetrahydrofurfuryl alcohol and 42 mL of 100 g / L polyvinyl alcohol, stirring until completely homogeneous. Allow to stand and sonicate to eliminate bubbles to obtain a uranium colloidal solution containing an organic carbon source.
[0060] 2. Vibration dispersion molding: The colloidal solution containing carbon source is transported to the pipeline by gas, then dispersed into droplets by the vibrator, and then passed through the air zone and the ammonia zone in sequence, and finally fell into the ammonia water to form gel microspheres.
[0061] 3. Aging, Washing, and Drying: The gel microspheres were soaked in concentrated ammonia solution for 14 hours. They were then washed with dilute ammonia solution at room temperature until the conductivity remained constant, followed by washing seven times with deionized water. After equilibration with deionized water for 4 hours, the conductivity of the washing solution was measured to be 8 μS / cm. The washed gel microspheres were then spread in a monolayer and transferred to a drying oven. The following stepped heating program was set: heating rate of 0.5°C / min, holding at 80°C for 0.5 hours, holding at 90°C for 1 hour, holding at 100°C for 2 hours, holding at 200°C for 2 hours, and cooling rate of 2°C / min to obtain intact dried gel microspheres.
[0062] 4. Sintering: The dried gel microspheres were transferred to a high-temperature furnace. A vacuum was first created, followed by the introduction of a certain amount of argon gas to maintain a positive pressure within the furnace tube. The argon gas flow rate was 90 L / h. The heating program was as follows: room temperature to 400°C, 3°C / min, hold for 1 hour; 450°C to 800°C, 3°C / min, hold for 1 hour; 800°C to 1200°C, 3°C / min, hold for 1 hour; 1200°C to 1600°C, 3°C / min, hold for 1 hour; 1600°C to 1950°C, 5°C / min, hold for 6 hours; 1950°C to room temperature, allow to cool naturally. Black UCO ceramic microspheres with a iridescent ceramic luster were obtained, with a density of 96% TD. At this point, the UC content was 35.5%, and the UO2 content was 64.5%.
[0063] Compared to Example 1, Example 2 used different uranium oxide raw materials (i.e., replacing UO2 with U3O8), different uranium concentrations, and different heating rates in the drying process, thus extending the final sintering temperature and holding time. However, the experimental results showed that different uranium oxide raw materials had no significant effect on the preparation of the colloid. Microspheres with good sphericity could be prepared within the initial uranium concentration range specified in this paper, and the higher the uranium ion concentration within the specified range, the better the sphericity. Reducing the heating rate in the drying process effectively reduced the microsphere breakage rate during drying; extending the sintering temperature and holding time, to some extent, increased the density of the final sintered microspheres.
[0064] Example 3:
[0065] According to this embodiment, a UCO ceramic microsphere is prepared by the following method:
[0066] 1. Preparation of uranium colloid: Weigh 45.91 g of UO2 powder and dissolve it in 6 mol / L nitric acid at 90°C to prepare 100 mL of a 1.7 mol / L uranyl nitrate solution. Heat to 90°C and slowly add 30.62 g of urea in batches, stirring until completely dissolved to form a yellow, transparent uranium sol solution. Cool to room temperature and disperse 9.98 g of ascorbic acid into the colloidal solution, stirring for about 2 hours until fully dissolved. Then, adjust the pH to 2.2 by adding ammonia dropwise. While stirring, add 10 mL of tetrahydrofurfuryl alcohol and 41 mL of 100 g / L polyvinyl alcohol, stirring until completely homogeneous. Let stand and sonicate to eliminate bubbles to obtain a uranium colloidal solution containing an organic carbon source.
[0067] 2. Vibration dispersion molding: The colloidal solution containing carbon source is transported to the pipeline by gas, then dispersed into droplets by the vibrator, and then passed through the air zone and the ammonia zone in sequence, and finally fell into the ammonia water to form gel microspheres.
[0068] 3. Aging, Washing, and Drying: The gel microspheres were soaked in concentrated ammonia solution for 12 hours. They were then washed with dilute ammonia solution at room temperature until the conductivity remained constant, followed by six washes with deionized water. After equilibration with deionized water for 5 hours, the conductivity of the washing solution was measured to be 6 μS / cm. The washed gel microspheres were then spread in a monolayer and transferred to a drying oven. A stepped heating program was set as follows: heating rate of 0.8°C / min, holding at 80°C for 0.5 hours, holding at 90°C for 0.5 hours, holding at 100°C for 2 hours, holding at 200°C for 3 hours, and cooling rate of 2°C / min to obtain intact, dried gel microspheres.
[0069] 4. Sintering: The dried gel microspheres were transferred to a high-temperature furnace. A vacuum was first created, followed by the introduction of a certain amount of argon gas to maintain a positive pressure within the furnace tube. The argon gas flow rate was 100 L / h. The heating program was as follows: room temperature to 400°C, 3°C / min, hold for 1 hour; 450 to 800°C, 3°C / min, hold for 1 hour; 800°C to 1200°C, 3°C / min, hold for 1 hour; 1200°C to 1600°C, 3°C / min, hold for 1 hour; 1600°C to 1900°C, 5°C / min, hold for 5 hours; 1900°C to room temperature, allow to cool naturally. Black UCO ceramic microspheres with a iridescent ceramic luster were obtained, with a density of 89% TD. At this point, the UC content was 14.1%, and the UO2 content was 85.9%.
[0070] Compared with Examples 1 and 2, Example 3 mainly investigated the changes brought about by using different [C] / [U] ratios to prepare microspheres. The experimental results showed that by adjusting the [C] / [U] ratio of the carbon source, the ratio of UC and UO2 in the sintered UCO product can be effectively controlled. However, other carbon sources such as sucrose and glucose will lose carbon source during the water washing process, which will lead to the uncontrollable microstructure uniformity of the final product and the ratio of UC to UO2 components.
[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention. Various variations can be made to the above embodiments of the present invention. That is, all simple and equivalent changes and modifications made based on the claims and description of this invention fall within the protection scope of the claims of this patent. All aspects not described in detail in this invention are conventional technical content.
Claims
1. A method for preparing a UCO fuel core, characterized in that, Includes the following steps: S1, under heating conditions, nitric acid is added to UO2 or U3O8 powder to dissolve and form uranyl nitrate solution. Urea is added and heated to react and form hydrolysis solution. Organic acid-based organic carbon source that can chelate with uranium ions is added to the hydrolysis solution and stirred thoroughly to disperse it evenly. Ammonia water is added dropwise to adjust the pH of the solution to 2.1~2.
5. Tetrahydrofurfuryl alcohol and thickener polyvinyl alcohol solution are added and stirred to form a uranium-based precursor solution containing organic carbon source. S2, the uranium-based precursor solution containing organic carbon source is dispersed into droplets by a vibrator, and the droplets fall into ammonia water after passing through an air section and an ammonia section in sequence to form gel microspheres; S3, the gel microspheres are placed in concentrated ammonia water and allowed to stand for aging. They are first washed with dilute ammonia water until the conductivity remains unchanged, and then washed with deionized water. The washed gel microspheres are then spread in a single layer in a drying oven and dried using a step-by-step temperature increase program to obtain dried gel microspheres. S4, the dried gel microspheres are placed in a sintering furnace and sintered under an inert gas atmosphere to obtain a UCO fuel core containing UO2 and UC components.
2. The preparation method according to claim 1, characterized in that, In step S1, the uranyl nitrate solution is an acid-deficient uranyl nitrate solution, and its preparation process includes: dissolving UO2 or U3O8 powder with nitric acid, stirring and heating to 75~90℃, slowly adding solid urea in batches to the uranyl nitrate solution for hydrolysis reaction for 36~50h, cooling to room temperature after the reaction is completed, and then adding the organic acid organic carbon source; the uranium-based precursor solution containing the organic carbon source needs to be ultrasonically degassed before dispersion to eliminate bubbles.
3. The preparation method according to claim 2, characterized in that, In step S1, the concentration of the uranyl nitrate solution is 1.4~2.2 mol / L; the molar ratio of urea / U(VI) is (2~3.4):1; and the molar ratio of nitric acid to UO2 powder is (1.7~1.9):
1.
4. The preparation method according to claim 1 or 2, characterized in that, In step S1, the organic acid-based organic carbon source capable of chelating with uranium ions is selected from any one of ascorbic acid, citric acid, malic acid, and tartaric acid; the molar ratio of carbon content to uranium metal ions in the organic acid-based organic carbon source [C] / [U] is (0.5~3.5):
1.
5. The preparation method according to claim 4, characterized in that, The organic carbon source of the organic acid is ascorbic acid.
6. The preparation method according to claim 1 or 2, characterized in that, In step S1, the concentration of the polyvinyl alcohol solution is 80~120g / L, and it is added to the hydrolysis solution at 10~30℃. The viscosity of the carbon-source-containing uranium-based precursor solution was adjusted using a viscometer to achieve a viscosity of 30-50 mPa·s at 25°C, and the concentration of polyvinyl alcohol in the precursor solution was 25-60 g / L.
7. The preparation method according to claim 1, characterized in that, In step S2, the uranium-based precursor solution containing an organic carbon source is transported to the pipeline by a constant flow pump, the flow rate of which is 3~10 mL / min; the frequency of the exciter is 20~50 Hz; the diameter of the needle used to disperse the droplets is 0.34~0.51 mm; and the ammonia flow rate in the ammonia section is 5~30 L / h.
8. The preparation method according to claim 1, characterized in that, In step S3, the concentration of the concentrated ammonia solution is 8-14 mol / L, and the gel microspheres are aged at 10-30℃ for 8-12 hours. When washing with deionized water, the nitrate ion content in the washing solution is first detected to be less than 10 mg / L, and then washing continues until the conductivity of the washing solution is less than 10 μS / cm after equilibration for 3-6 hours. The heating rate of the step-programmed temperature drying is 0.3-1℃ / min, and the temperature is maintained at 80℃ and 90℃ for 0.5-1 hours each, and at 100℃ and 200℃ for 2-3 hours each.
9. The preparation method according to claim 1, characterized in that, In step S4, the inert gas is nitrogen or argon, and the furnace tubes of the sintering furnace are kept under positive pressure. The inert gas flow rate is 70~100 L / h. The heating sintering includes calcination and densification sintering. The calcination heating program is from room temperature to 1600℃, with a heating rate of 3℃ / min, and holding at 400℃, 800℃, 1200℃, and 1600℃ for 1 hour each. The densification sintering is from 1600 to 1950℃, with a heating rate of 5℃ / min, and holding for 3~6 hours.
10. The preparation method according to claim 1, characterized in that, The UCO fuel core is UCO ceramic microspheres with a diameter distribution of 300μm~1.0mm. The ratio of UO2 to UC components in the UCO ceramic microspheres can be controlled by adjusting the amount of organic acid-based organic carbon source added, and the microsphere density reaches 69.9%~97% of the theoretical density.